The environmental impacts of/on second homes on/in Hartbeespoort dam, South Africa - Long, Dianne Patricia (My University, 2014)
Tourism and the environment are two interdependent entities, for tourism to thrive the environment needs to be sustained, conversely for the environment to be sustained tourism needs to attain to the goals of responsible tourism. Second home tourism research has shown that scenic natural environments influence the location and development of second homes, however, little attention has been paid to the potential impact degraded environments can have on second home tourism and more specifically their owners. Second home tourism studies have also found that there are environmental concerns which arise through the development and continued use of a second home. The majority of these studies, however, have been conducted in the Global North, and no research of this kind has yet been conducted in South Africa. This study aims to fill these gaps in the South African understanding of second home tourism by looking at the relationship that exists between the environment and second homes using Hartbeespoort in the North West Province of South Africa as the case study. The impacts associated with the degraded environment of Hartbeespoort on second homes include the decline in property values of second homes, their recreational place utility and consequently the place attachment value of the owners. Potential knock-on effects include the undermining of second home tourism, which directly affects the local economy of Hartbeespoort. Knowing the implications of a degraded environment for second home tourism may incite more responsible behaviour by tourists themselves in addition to an improved tourism policy by government and the acknowledgement of the importance of the natural environment across municipal and provincial boundaries. In terms of the environmental impacts of second homes, special attention was paid to the perceptions held by second home owners. The perception held by the majority of Hartbeespoort second home owner respondents is that neither they, nor their households, impact upon the environment. This perception brings the environmental sustainability of second home tourism in South Africa into question. However, the case is not so, as second homes in Hartbeespoort do impact upon the environment, through their initial development and continued use. These impacts need to be acknowledged in order for successful mitigation strategies to be put in place. Understanding these impacts, therefore, is essential for policy, planning and mitigation in order to attain to the goal of responsible tourism so sought after by the South African government.